Gender difference in performance of undergraduate medical students for subjective and objective evaluation in physiology - Sinha, Meenakshi; Ghate, Jayshri; Chatur, Dipali K.; Sinha, Ramanjan (International Journal of Scientific Reports, 2017)
Background: Several studies have indicated gender differences in performance of undergraduate students in medical curriculum mainly in the clinical specialties which requires different set of skills as compared to pre and paraclinical subjects. Therefore, the study aim to investigate gender difference if any, on overall performance as well as on different modalities of assessment like multiple choice questions (MCQ) and structured long & short answer questions (LSQ) of medical students in physiology. Methods: Performance of 238 first year MBBS students in overall theory (MCQ+LSQ) and separately in MCQ and LSQ were compared between male (n=139) & female (n=99). Further, they were sub-grouped on the basis of total marks in theory as low (<50%), medium (50-65%) and high achievers (>65%). Results: Female students scored significantly more compared to male students in total (60.8±7.42% vs 56.81±8.78%) as well as individually in MCQ & LSQ. Also, overall failure rate was more for male (19%) as compared to female (7%). However, comparison of high achiever group revealed no significant difference in performance of both genders in all modalities of assessments. Whereas, female students of both medium and low achiever groups had significantly high scores in LSQ as compared to male, but no such difference was observed for MCQ. Conclusions: Average and below average female students performed better relative to their male counterparts in subjective assessment (LSQ) as compared to assessment demanding more analytical/critical thinking (MCQ). However, performance of high achievers did not show any such gender difference. Therefore, different types of assessments bring out different abilities of students across genders depending on their grade of performance in a medical curriculum.